Germination and germination energy of pale purple coneflower (Echinacea pallida(Nutt.) Nutt.) depending on the influence of stimulants - Григоришин, Є. В. (Scientific Progress & Innovations, 2017)
In article influence of environmentally safe stimulants on the germination and germination energy of pale purple coneflower were investigated. It has been established that the age of the seeds, how to handle it, additional processing gibberellin define 95 % variation in germination and 92 % of the variation in the germination energy of pale purple coneflower seeds. We obtained data indicating that germination energy and germination of new seeds in 4–5 times higher than the old ones. Gibberellin processing significantly stimulates these indicators. We confirmed that among the ways most efficient seed pretreatment effects on germination and germination of seeds carries out UHF electromagnetic field. The influence of other treatments is evident in comparison with control, but less than in the case of the UHF. Ultra-high-frequency electromagnetic field in the investigated range of timing of exposure demonstrates a positive dose-dependent efficacy.